2020
DOI: 10.5021/ad.2020.32.2.164
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cutaneous Leukocytoclastic Vasculitis Associated with Granulocyte Colony-Stimulating Factor: An Unusual Presentation

Abstract: Drug-induced vasculitis is an inflammation of small-sized blood vessel caused by the use of drugs. It accounts for approximately 10% of acute cutaneous vasculitis. Propylthiouracil, hydralazine, and allopurinol have been widely known as causative agents. The most common clinical feature of drug-induced vasculitis is palpable purpura on lower extremities. A 66-year-old Korean female presented with erythematous nodules on upper chest and back. She had been on medication for multiple myeloma. Laboratory results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…From a dermatological standpoint, G-CSF therapy has been linked to various manifestations, such as pyoderma gangrenosum [58], Sweet's syndrome [59][60][61][62][63][64][65], other neutrophilic dermatoses [66], granulomatous dermatitis [67], widespread folliculitis [68], cutaneous vasculitis [50,[69][70][71][72], and exacerbations of acne [73] and psoriasis [70,74,75]. Several cases of cutaneous eruptions containing leukemic cells have been reported (without their presence in the bone marrow or blood) after G-CSF, suggesting the skin's ability to simulate malignancies, as well as its dependency on G-CSF administration [76,77].…”
Section: Adverse Reactions To G-csfmentioning
confidence: 99%
“…From a dermatological standpoint, G-CSF therapy has been linked to various manifestations, such as pyoderma gangrenosum [58], Sweet's syndrome [59][60][61][62][63][64][65], other neutrophilic dermatoses [66], granulomatous dermatitis [67], widespread folliculitis [68], cutaneous vasculitis [50,[69][70][71][72], and exacerbations of acne [73] and psoriasis [70,74,75]. Several cases of cutaneous eruptions containing leukemic cells have been reported (without their presence in the bone marrow or blood) after G-CSF, suggesting the skin's ability to simulate malignancies, as well as its dependency on G-CSF administration [76,77].…”
Section: Adverse Reactions To G-csfmentioning
confidence: 99%
“…A cutaneous manifestation, such as papulonodular eruptions, is unusual for LV, with the exception of erythema elevatum diutinum, which may occur in association with hematologic diseases and malignancies 9 . However, multiple nodules associated with LV have been reported in a multiple myeloma patient receiving G‐CSF, 10 and the spontaneous healing after the cessation of lenograstim indicated that erythema elevatum diutinum could be excluded. A high immunoglobulin level was regarded as one of the predisposing factors for LV 3 .…”
Section: Figurementioning
confidence: 99%